Development of a bio-retention system for urban storm water management. Issue 1 (November 2021) - Reddy, Polimerra Venkata Koti; Kumar, Pramod; John, Siby
Abstract: Urban stormwater that flows through all the manmade structures contains high levels of BOD TSS, orthophosphate, surfactants etc. It raises concerns of water quality in the receiving natural water courses. Bio-retention is one of the prominent methods of stormwater management for the removal of contaminants from stormwater. In this esxperimental study, a column containing mulch, blast furnace slag, sand, silt etc. was used to assess the removal of suspended solids and nutrients (nitrate and phosphate) from stormwater. The tests were conducted with a flow through period of 3, 7 and 15 days. Removal efficiency of 80% total suspended solids for 15 day, 60% nitrate for 7 days and 70% phosphorous for 3 and 7 days was observed through the column. pH variation was found to be insignificant in the range of 6-7.5.